Pre–Post Changes in Anemia Knowledge and Attitudes Following HPM-Informed E-Booklet Education Among Adolescent Girls - Wulan Novika Ambarsari; Ayu Apriyani; Rudi Karmi; Rahayu Savitri (STIKes Budi Luhur Cimahi, 2026)
Anemia is a reduction in hemoglobin concentration below an age-, sex-, and physiological-status-specific threshold and may result from nutritional deficiencies, blood loss, inflammation, inherited disorders, or other causes. Menstruating adolescent girls are a priority population for prevention and educational interventions. This study aimed to assess immediate pre-post changes in knowledge and attitudes toward anemia following an e-booklet educational intervention informed by Pender's Health Promotion Model (HPM). A quantitative one-group pretest-posttest study was conducted among 77 adolescent girls at SMK Pasundan 3 Cimahi. Participants were selected from a population of 327 students using proportionate stratified random sampling. Recruitment and consent/assent were followed by a pretest assessment, standardized e-booklet education, and an immediate posttest. Knowledge was categorized as good, fair, or poor, while attitudes were categorized as positive or negative. Data were analyzed using the Marginal Homogeneity and McNemar tests. The proportion of participants with good knowledge increased from 16.9% to 79.2% (absolute change: +62.3 percentage points), while poor knowledge decreased from 58.4% to 2.6% (p < 0.001). Positive attitudes increased from 54.5% to 76.6% (absolute change: +22.1 percentage points; p = 0.005). Knowledge and attitude categories were more favorable immediately after the e-booklet intervention. Because the study lacked a comparison group and assessed outcomes only immediately after the intervention, controlled studies with validated continuous measures and longer follow-up are needed to establish the effectiveness and sustainability of the observed changes.